THE EFFECT OF GUIDANCE AND COUNSELING MANAGEMENT ON STUDENT CHARACTER DEVELOPMENT IN THE MERDEKA CURRICULUM - Ibrahim, Tatang (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The background of this study focuses on the crucial role of character education in shaping the morals and personality of students, particularly within the context of Madrasah Aliyah in Bandung Regency. With the evolving social challenges, a systematic approach to guidance and counseling is essential to support the character development of students. Purpose: The purpose of this study was to identify the influence of guidance and counseling management on the character development of students in Madrasah Aliyah in Bandung Regency. Method: This study uses a quantitative approach to the survey method. Data analysis techniques were carried out through observation, interviews, documentation, and questionnaires which were distributed to 37 guidance and counseling teachers. Result: The results showed that there was a significant influence between the management of counseling guidance and the character development of students in Madrasah Aliyah in Bandung Regency by 23.6% and the remaining 76.4% was influenced by other variables not examined, with T_hitung 5,581 >T_tabel (0,682and a significant value of 0,000<0,05. Conclusion: The results of this study indicate that effective guidance and counseling management can be the key to improving student character development